Early Mobilization Education for Families of Postoperative Lower Extremity Fracture Patients to Support Independence in Daily Activities - Syara, Arfah May; Yanti, Dian Anggri; Lumban Tobing, Putri Diana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2025)
The incidence of lower extremity fractures is significantly high in healthcare facilities, particularly among elderly patients and those suffering from injuries caused by accidents. Post-surgical patients often experience difficulty performing daily activities such as walking and changing positions. Early mobilization has been shown to facilitate faster physical recovery and reduce the risk of various complications. This community engagement program aimed to enhance the knowledge and skills of patients' families in supporting proper and safe early mobilization. The program employed a participatory educational approach to train family caregivers in early mobilization techniques. The activity began with a pre-test and concluded with a post-test to measure participants' knowledge improvement. Participants were selected through purposive sampling based on inclusion criteria, resulting in a total of 30 participants. The results indicated a 37.8 point increase (72.3%) in participants’ knowledge and a 93% improvement in their practical skills, with most classified as highly capable or adequately capable in performing basic mobilization procedures. Additionally, participants expressed high satisfaction with the educational intervention, with an average satisfaction score of 4.5, reflecting excellence in material clarity, content relevance, media quality, facilitator competence, and overall program benefit. In conclusion, this community service program successfully improved participants’ knowledge by 72.3%, skills by 93%, and satisfaction with the educational activities by a mean score of 4.5.